2000
DOI: 10.1074/jbc.m005785200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Kinetics of Regulator of G-protein Signaling (RGS)-mediated Gαi and Gαo Deactivation

Abstract: Regulator of G-protein signaling (RGS) proteins accelerate GTP hydrolysis by G␣ subunits speeding deactivation. G␣ deactivation kinetics mediated by RGS are too fast to be directly studied using conventional radiochemical methods. We describe a stopped-flow spectroscopic approach to visualize these rapid kinetics by measuring the intrinsic tryptophan fluorescence decrease of G␣ accompanying GTP hydrolysis and G␣ deactivation on the millisecond time scale. Basal k cat values for G␣ o , G␣ i1 , and G␣ i2 at 20°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 46 publications
8
84
1
Order By: Relevance
“…5 for additional examples). In contrast, some RGS proteins, like RGS4, seem to be rather nonspecific in interacting with their G␣ partners (5,26).…”
Section: Rgs9-1⅐g␤5l Is a Useful Model For Studying The Specificity Imentioning
confidence: 97%
See 1 more Smart Citation
“…5 for additional examples). In contrast, some RGS proteins, like RGS4, seem to be rather nonspecific in interacting with their G␣ partners (5,26).…”
Section: Rgs9-1⅐g␤5l Is a Useful Model For Studying The Specificity Imentioning
confidence: 97%
“…It has been shown that the catalytic domain of RGS7 stimulates the GTPase activities of G␣ i and G␣ o with equal efficiencies (26,30) whereas the full-length RGS7⅐G␤5 complex stimulates the GTPase activity of only G␣ o (5,30). Thus, the primary role of the noncatalytic domains of RGS9-1⅐G␤5L in determining its substrate specificity is likely to reflect a general principle in RGS protein functioning.…”
Section: Rgs9-1⅐g␤5l Is a Useful Model For Studying The Specificity Imentioning
confidence: 99%
“…This idea is consistent with a model in which the receptor, G protein, and RGS do not physically dissociate but, rather, go through a series of conformational changes while progressing through the functional cycle. Such a model helps explain the rapid kinetics of many G protein cascades and the sub-second time constant of RGS-G␣ interactions (36). At this point it is not clear whether the dynamics of RGS-G␣ binding was not detected due the technical limitations of CFP-YFP FRET method or due to the true properties of G␣ q -G␤5⅐RGS7 complex in cells.…”
Section: Function Of G␤5⅐rgsmentioning
confidence: 99%
“…The maximal stimulation of GTP hydrolysis by 10 M morphine at 2 min was 45 Ϯ 5% in the C6-G␣ o PTXi membranes and increased significantly (p Ͻ 0.05) to 94 Ϯ 17% in the presence of 1 M GST-RGS8, although relative to DAMGO, morphine was significantly less efficacious (p Ͻ 0.05) in the presence of GST-RGS8 (61 Ϯ 3%) than in its absence (75 Ϯ 1%). RGS8 was chosen for these studies because it is structurally a simpler RGS protein and is known to be a GAP for G␣ o (22).…”
Section: Methodsmentioning
confidence: 99%